African Instrumentation in Musicals: From Traditional Drums to Modern Electronics – An Analysis of the Use of African Instruments in Musicals and Their Influence on Musical Arrangement - Mański, Szymon (Interdisciplinary Studies in Musicology, 2026)
This article examines the use of African instruments in contemporary musicals, from traditional drums and percussion to modern electronic forms inspired by African rhythms. These instruments are not merely elements of ethnic decoration but also serve a significant narrative, emotional, and identity-building function. The article examines musicals like The Lion King, Fela!, and Once on This Island, where African sounds become integral to the storytelling and mood-building. The analysis aims to demonstrate how African instruments enrich the musical form with unique cultural and rhythmic layers that would be difficult to achieve using only Western instrumentation. The text also demonstrates how African influences permeate modern arrangements, combining ethnic traditions with innovation.